2014
DOI: 10.4269/ajtmh.12-0547
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Screening of Compounds against Laboratory and Field Isolates of Human Hookworm Reveals Quantitative Differences in Anthelmintic Susceptibility

Abstract: Abstract. A panel of 80 compounds was screened for anthelmintic activity against a laboratory strain of Ancylostoma ceylanicum and field isolates of hookworm obtained from school children in the Kintampo North District of the Brong Ahafo Region of Ghana. Although the laboratory strain of A. ceylanicum was more susceptible to the compounds tested than the field isolates of hookworm, a twofold increase in compound concentration resulted in comparable egg hatch percent inhibition for select compounds. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…Conoidin A inhibits TgPrxII with an IC 50 of 23 μM by binding covalently to the peroxidatic cysteine (Liu, et al, 2010). More relevant to the present study, conoidin A treatment of A. ceylanicum eggs purified from the feces of infected hamsters as well as eggs from field isolates of human hookworms resulted in a significant inhibition of egg hatching, revealing the nematicidal activity of conoidin A (Treger, et al, 2013). …”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Conoidin A inhibits TgPrxII with an IC 50 of 23 μM by binding covalently to the peroxidatic cysteine (Liu, et al, 2010). More relevant to the present study, conoidin A treatment of A. ceylanicum eggs purified from the feces of infected hamsters as well as eggs from field isolates of human hookworms resulted in a significant inhibition of egg hatching, revealing the nematicidal activity of conoidin A (Treger, et al, 2013). …”
Section: Introductionmentioning
confidence: 65%
“…Our observation that AcePrx-1 is predominately expressed in adult hookworms and not in egg or larval stages suggests that inhibition of egg hatching by conoidin A (Treger, et al, 2013) may occur through inhibition of a protein other than AcePrx-1. A second peroxiredoxin has been identified in A. ceylanicum but its expression pattern and biochemical activity have not yet been studied.…”
Section: Discussionmentioning
confidence: 90%
“…34,35 All study medications were administered under direct observation by GHS Pharmacists based at the Kintampo Health Center on one of two treatment days (June 24 or June 30, 2011), and the anthelminthic activity of the albendazole preparation used in the study was confirmed in the field using an in vitro assay. 43 Stool specimens were collected from treated individuals 10-14 days later and evaluated by fecal microscopy using the Kato-Katz method as described above. This time point was chosen to measure the effect of treatment on fecal egg excretion before reinfection.…”
Section: Methodsmentioning
confidence: 99%
“…The overall structural connectivity was established by HSQC, HMBC, and COSY spectroscopic data (Figures S2–S6, Supporting Information) and by comparison with known compounds. 28,30 ECD data were used to define the absolute configuration at C-2 in compound 1 . The ECD spectrum (Figure S1, Supporting Information) showed sequential positive and negative Cotton effects near 350 and 310 nm for the n → π* and π → π* electronic transitions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 A panel of azole-inspired synthetic compounds, consisting of nitrogen- and oxygen-containing heterocycles (e.g., furoxan analogues), was tested against various A. ceylanicum isolates in a more recent study that revealed differences in susceptibility of laboratory versus field isolates of Ancylostoma spp. 28 …”
mentioning
confidence: 99%